Compliance With Guideline Statements for Urethral Catheterization in an Iranian Teaching Hospital - Negar Taleschian-Tabrizi; Fereshteh Farhadi; Neda Madani; Mohaddeseh Mokhtarkhani; Kasra Kolahdouzan; Sakineh Hajebrahimi (Kerman University of Medical Sciences, 2015)
Background It is believed that healthcare staff play an important role in minimizing complications related to urethral catheterization. The purpose of this study was to determine whether or not healthcare staff complied with the standards for urethral catheterization. Methods This study was conducted in Imam Reza teaching hospital, Tabriz, Iran, from July to September 2013. A total of 109 catheterized patients were selected randomly from surgical and medical wards and intensive care units (ICUs). A questionnaire was completed by healthcare staff for each patient to assess quality of care provided for catheter insertion, while catheter in situ, draining and changing catheter bags. Items of the questionnaire were obtained from guidelines for the prevention of infection. Data analysis was performed with SPSS 16. Results The mean age of the patients was 50.54 ± 22.13. Of the 109 patients, 56.88% were admitted to ICUs. The mean duration of catheter use was 15.86 days. Among the 25 patients who had a urinalysis test documented in their hospital records, 11 were positive for urinary tract infection (UTI). The lowest rate of hand-washing was reported before bag drainage (49.52%). The closed drainage catheter system was not available at all. Among the cases who had a daily genital area cleansing, in 27.63% cases, the patients or their family members performed the washing. In 66.35% of cases, multiple-use lubricant gel was applied; single-use gel was not available. The rate of documentation for bag change was 79%. Conclusion The majority of the guideline statements was adhered to; however, some essential issues, such as hand hygiene were neglected. And some patients were catheterized routinely without proper indication. Limiting catheter use to mandatory situations and encouraging compliance with guidelines are recommended.